There is an error in the process of completing the square on the left hand side while going from line 3 to line 4, since

`b^2+1/2b+(1/2)^2!=(b+1/2)^2.`

A correct solution starting at line 3 would be

`b^2+1/2b+(1/4)^2=3+(1/4)^2`

`(b+1/4)^2=3+1/16`

`b+1/4=+-sqrt(49/16)`

`b=-1/4+-7/4`.

This gives the two solutions `b=3/2` and `b=-2.`

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

There is an error in the process of completing the square on the left hand side while going from line 3 to line 4, since

`b^2+1/2b+(1/2)^2!=(b+1/2)^2.`

A correct solution starting at line 3 would be

`b^2+1/2b+(1/4)^2=3+(1/4)^2`

`(b+1/4)^2=3+1/16`

`b+1/4=+-sqrt(49/16)`

`b=-1/4+-7/4`.

This gives the two solutions `b=3/2` and `b=-2.`